Factors affecting patient readiness and surgical outcomes in preoperative patients a model testing study - Torres, Gian Carlo Sy (Manila College of Nursing, University of the Philippines Manila, 2017)
Background: Surgery is a common approach to manage various disorders among patients across the lifespan. However, being an unknown and complex procedure for most, it may lead to stress and anxiety, both to the patient and their significant others. Nurses, being at the forefront of patient care, must ensure adequate preparation to promote patient readiness.Albeit studies claim the importance of readiness, there is paucity of evidence supporting such notion.

Purpose: This study was intended to develop and validate a model that shows the interrelationships between readiness and surgical outcomes and the factors that can affect patient readiness.

Methods: The study utilized a descriptive correlational design and recruited 376 surgical patients from four tertiary medical institutions in Metro Manila, Philippines. A six-part survey package composed of the Basic Information Sheet, Newest Vital Signs tool, Preoperative Intrusive Thoughts Inventory, Pre-operative Assessment of Readiness Tool, Consumer Assessment of Healthcare Providers and Systems Surgical Care Survey questionnaire, and Post-Operative Assessment Checklist, was utilized to assess pre-operative data within 24-hours before the surgery and post-operative information within 48 to 72 hours after surgery. Data were analyzed using descriptive statistics, Covariance-based Structural Equation Modeling, and path analysis.

Results: After model trimming, the emerging model showed good fit indices: x²/df=0.75, RMSEA=0.00, GFI=0.99, CFI=1.00, and PNFI=0.50. Patient readiness directly influenced surgical outcomes, such as use of rescue pain medications (=-0.05, =0.010), surgical satisfaction (=0.18, =0.004), and development of surgical complications (OR=1.04, =0.0004). Preoperative factors, such as type of surgery (=0.09, =0.004), positively influences readiness while preoperative anxiety (=-0.25, =0.004) and health literacy (=-0.07, =0.007) negatively affect readiness. Result also confirmed the mediating role of patient readiness in the influence of the type of surgery, health literacy, and preoperative anxiety to different surgical outcomes.

Discussion: The type of surgery to be performed and the patients’ health literacy and pre-operative anxiety levels affect the latter’s surgical readiness. Patient readiness influences surgical outcomes such as development of post-operative complications, need for rescue pain medications, and the degree of satisfaction. Readiness is also an important mediator that affects patient outcomes observed after surgery. The concept of patient readiness has been validated by qualitative interviews highlighting items similar in the Pre-operative Assessment of Readiness Tool and identified readiness-promoting actions. Meanwhile, factors identified in the qualitative interviews showed how anxiety is a major factor which influences patient readiness and how establishing a sense of control is essential in overcoming the negative influence of anxiety. Moreover, patient readiness is an essential element that healthcare providers must established before surgical procedures, as it can lead to a patient who is more in control, can appropriately acknowledge his or her pain experience, knows when to ask for additional pain medication, and are generally more satisfied with their surgical experience.

Conclusion: The model developed is a parsimonius and theoretically-sound, which reflects that readiness is a significant factor that can promote the development of better surgical outcomes. Further, adequate patient readiness can positively mediate the influence of anxiety and health literacy to have better surgical outcomes. Therefore, it is essential for healthcare providers to develop appropriate programs that are patient-specific and individualized surgical care to ensure adequate preparation among surgical patients.
Dissertation (Doctor of Philosophy in Nursing) -- University of the Philippines Manila, November 2017.
Bibliography: leaves 113-125.
Keywords: Patients -- Preparedness; Preoperative care